Efforts to Improve the Ability of Mastering the Concept of Number Using Number Bag Media in Children Aged 4–5 Years in PAUD Kita Jaya Beach District is a Mirror for 2021/2022 Academic Year - Ayu Sepvina; Juli Yanti Harahap (International Journal of Educational Research Excellence (IJERE), 2022)
The main problem in this study is how to increase the ability to master the concept of numbers by using Number Pocket Media in our PAUD Jaya Pantai Cermin. This study aims to improve the ability to master the concept of numbers by using Number Pocket Media in our PAUD Jaya Pantai Cermin. This type of research is class action research (Classroom Action Research) which consists of two cycles in each cycle there are three meetings. Research procedures include planning, implementation, observation, and reflection. The subjects in this study were students aged 4-5 years at Kita Jaya Pantai Cermin PAUD, totaling 13 children. The results of this study can be concluded that the increase is seen in the first cycle of meetings I to III students are at the MB development level (Starting to Develop) with an average value of 46%. Then the second cycle of meetings I to III was carried out so that there was an increase to 94%, which means that the average child is already at the level of development of BSH (Developing According to Expectations). at Kita Jaya Pantai Cermin Beach.